Research Progress on the Mechanism of Acupuncture in the Treatment of PTSD - Zhang, Xuanyu; Han, Jing; Lin, Li; Shi, Yusu; Li, Yongfeng (Journal of Contemporary Medical Practice, 2024)
At present, there is a lot of room for increase in acupuncture treatment of Post-traumatic Stress Disorder, both in terms of research and the number of articles published. This article reviews the clinical and mechanism of acupuncture treatment of PTSD at home and abroad in recent years. Clinical studies have shown that acupuncture can effectively alleviate PTSD-related symptoms and is an effective means of treating PTSD. Experimental studies have shown that the mechanism of acupuncture therapy for PTSD may involve regulating neural loops, neurotransmitter and receptor expression, signaling pathways, apoptosis, immune cytokin and endogenous cannabinoids. This can provide a reference basis for the clinical application of acupuncture treatment of PTSD and provide new ideas for future in-depth clinical research.